Coleophora ericarnella Baldizzone, a new species of the C. pyrrhulipennella group (Lepidoptera: Coleophoridae) from the South-Eastern Alps - Baldizzone, Giorgio; Landry, Jean-François (Zootaxa, 2016)
Coleophora ericarnella Baldizzone, n. sp. is described from the East-Central Alps region (Italy and Slovenia). It belongs to the C. pyrrhulipennella group. Its larval host plant is Erica carnea (Ericaceae). The adult habitus and genitalia as well as its larval case are illustrated and compared with those of Coleophora pulchripennella Baldizzone, 2011 and C. pyrrhulipennella Zeller, 1849. DNA barcodes also distinguish all three species from each other in congruence with genitalia morphology.